Pengaruh Tata Letak (Layout) Terhadap Produktivitas Batu Bata di UD. MUSTIKA DESA LOLOWUA HILIWARASI Kecamatan Hiliserangkai Kabupaten Nias - Syukur Wildman Mendrofa; Jeliswan Berkat Iman Jaya Gea; Maria Magdalena Bate'e; Eduar Baene (LPPM Universitas HKBP Nommensen, 2024)
This study aims to analyze the impact of layout on the productivity of brick manufacturing businesses in Lolowua Hiliwarasi Village, Hiliserangkai District, Nias Regency. The research employs a quantitative approach, gathering data through observations and interviews with business owners and workers. The findings indicate that an efficient layout can enhance productivity by reducing travel time and minimizing disruptions in the production process. A well-designed layout facilitates workflow and improves the effectiveness of space and resource utilization. The study concludes that optimizing the layout of brick manufacturing operations can significantly boost productivity and operational efficiency.